L'ostréiculture en baie de Bourgneuf. Relation entre la croissance des huîtres Crassostrea gigas et le milieu naturel : synthèse de 1986 a 1995 - Barille-boyer, Anne-laure; Haure, Joel; Baud, Jean-pierre (1997)
The oyster growth has been studied for a 10 year period, from 1986 to 1995, in four locations of the bay of Bourgneuf (French Atlantic Coast). The relations between oysters growth and the main molluscs stocks (cultivated oysters and wild mussels) or environmental factors (hydrobiology, currents, climatology) are analysed to understand the functioning of this shellfish ecosystem. As the water renewal time is about two months, primary production is essentially autochtonal. Phytoplankton development is controlled by the nutrients brought by the river Loire. An important part of the microalgac is composed by the microphytobenthos resuspended by west wind. High seston concentrations, measured on the North of the bay (150 mg/1 as an average), have a negative influence on the feeding physiology of die oyster. The important food development of this area (20 ug/1 of chlorophyll a) cannot be fully exploited. The decrease of the oyster growth rate,observed since 1980, on the whole bay, is due to an overexpioitation induce by a too large cultivated oyster stock (45 to 50 000 tonnes). The cultural practices (concentration of oysters parks, double row of oysters tables, use of collector support for oyster growth) increase the oyster density and the overexpioitation. The oyster meat, produced during spring and summer, is lost during spawning. As fall blooms are exceptional, the oyster quality at the end of the year is not satisfactory. There is no recruitment in Bourgneuf bay, and more than 99 % of the spat come from Fouras in the bay of Marennes-Oléron. The oyster production seems to be independent from the oyster stock. New research and management axes arc proposed in order to improve the oyster quality in the bay of Bourgneuf. La croissance des huîtres de la baie de Bourgncuf est étudiée sur 10 ans, de 1986 à 1995, en quatre points de la baie. Ces croissances sont mises en relation avec les stocks des principaux mollusques de la baie (huîtres cultivées et moules sauvages) ainsi qu'avec les facteurs environnementaux ...